THE ROLE OF RESOURCE MISALLOCATION IN CROSS-COUNTRY DIFFERENCES IN MANUFACTURING PRODUCTIVITY. (8th January 2016) - Inklaar, Robert; Lashitew, Addisu A.; Timmer, Marcel P.
Abstract : Misallocation of resources across firms leads to lower aggregate productivity. In this paper, we provide new estimates of manufacturing productivity differences across countries and establish by how much they would be reduced if such misallocation were eliminated. Using World Bank survey data for formal manufacturing firms in 52 low- and middle-income countries, we show that manufacturing productivity would increase by an average of 62%, but productivity gaps relative to the United States would remain large. We also find that lower-income countries do not have more to gain from reducing misallocation, as efficiency of resource allocation is uncorrelated with income levels.